The effect of body mass index on clinical outcomes in patients with newly diagnosed atrial fibrillation in the GARFIELD-AF registry. (25th November 2020) - Camm, C.J.F; Camm, A.J; Virdone, S; Bassand, J.-P; Fitzmaurice, D.A; Fox, K.A.A; Goldhaber, S.Z; Goto, S; Haas, S; Turpie, A.G.G; Verheugt, F.W.A; Misselwitz, F; et al.
Abstract: Introduction: Higher body mass index (BMI) is associated with a higher risk of atrial fibrillation (AF). However, previous evidence has suggested an inverse association between BMI and risk of AF outcomes. Purpose: To explore the association between BMI and outcomes in those with newly diagnosed AF in the GARFIELD-AF registry. Methods: GARFIELD-AF is an international registry of consecutively recruited patients aged ≥18 years with newly diagnosed AF and ≥1 stroke risk factor. Data were collected prospectively on 52, 080 patients. Participants with missing or extreme BMI values and those without two-year follow-up were excluded. Cox proportional hazard models were used to estimate the effect of BMI on the risk of outcomes. Models were adjusted for age, sex, ethnicity, smoking, alcohol, and ≥moderate chronic kidney disease. Where appropriate participants were divided into groups based on BMI. Restricted cubic splines were used to assess non-linear relationships. Results: BMI and outcome data were available for 40, 495 patients. Those with higher BMI were generally younger, and more likely to have pre-existing hypertension, diabetes, or vascular disease (Table). Underweight patients received anticoagulation less often than those in other groups (60.3% vs 67.9%, respectively). During follow-up, 2, 801 participants (6.9%) died and 603 (1.5%) had new/worsening heart failure. Following adjustment for potential confounders, a U-shaped relationship was seen between BMI and all-cause mortality and new/worsening heart failure (Figure). For all-cause mortality, the lowest risk was at 30kg/m 2 . Below this level, there was an 8% higher risk of mortality (95% confidence interval (CI) 6 to 9%) per 1kg/m 2 lower BMI. Above 30kg/m 2, there was a 5% higher risk of mortality per 1kg/m 2 higher BMI (95% CI 4 to 7%). For new/worsening heart failure, the lowest risk was at 25kg/m 2 . Above this level, 1kg/m 2 higher BMI was associated with an 5% higher risk (95% CI 13 to 6%). Conclusions: BMI was an important risk factor for both all-cause mortality and new/worsening heart failure in AF. Those at both extremes of BMI are at higher risk. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): The GARFIELD-AF registry is funded by an unrestricted research grant from Bayer AG.